Redox-responsive self-assembled polymeric nanoprodrug for delivery of gemcitabine in B-cell lymphoma therapy. (May 2022) - Zhong, Wenhao; Zhang, Xinyu; Duan, Xiao; Liu, Hengyu; Fang, Yifen; Luo, Moucheng; Fang, Zhengwen; Miao, Congxiu; Lin, Dongjun; Wu, Jun
Abstract: Gemcitabine, as a standard and classic strategy for B-cell lymphoma in the clinic, is limited by its poor pharmacodynamics. Although stimuli-responsive polymeric nanodelivery systems have been widely investigated in the past decade, issues such as complicated procedures, low loading capacity, and uncontrollable release kinetics still hinder their clinical translation. In view of the above considerations, we attempt to construct hyperbranched polyprodrug micelles with considerable drug loading via simple procedures and make use of the particularity of the tumor microenvironment to ensure that the micelles are "inactivated" in normal tissues and "activated" in the tumor microenvironment. Hence, in this work, a redox-responsive polymeric gemcitabine-prodrug (GEM-S-S-PEG) was one-pot synthesized via facile esterification and acylation. The self-assembled subsize (< 100 nm) GEM-S-S-PEG (GSP NPs) with considerable loading capacity (≈ 24.6%) exhibited on-demand and accurate control of gemcitabine release under a simulated tumor microenvironment and thus significantly induced the apoptosis of B-cell lymphoma in vitro . Moreover, in the A20 tumor xenograft murine model, GSP NPs efficiently decreased the expansion of tumor tissues with minimal systemic toxicity. In summary, these redox-responsive and self-assembling GSP NPs with a facile one-pot synthesis procedure may hold great potency in clinical translation for enhanced chemotherapy of B-cell lymphoma. Statement of significance: A redox-responsive polymeric gemcitabine-prodrug (GEM-S-S-PEG) was one-pot synthesized via facile esterification and acylation. The self-assembled subsize (< 100 nm) GEM-S-S-PEG (GSP NPs) exhibited significant tumor therapeutic effects in vitro and in vivo . The polyprodrug GEM-S-S-PEG prepared in this study shows the great potential of redox-responsive nanodrugs for antitumor activity, which provides a reference value for the optimization of the design of functional polyprodrugs. Graphical abstract: Image, graphical abstract